Molecular characterization of Pacific white shrimp (Litopenaeus vannamei) sodium bicarbonate cotransporter (NBC) and its role in response to pH stress. Issue 64 (May 2017) - Cai, Yi-Ming; Chen, Ting; Ren, Chun-Hua; Huang, Wen; Jiang, Xiao; Gao, Yan; Huo, Da; Hu, Chao-Qun
Abstract: The sodium bicarbonate cotransporter (NBC) is an integral membrane ion transporter that can transport HCO3 − (or a related species, such as CO3 2- ) across the plasma membrane. Previous researches revealed that NBC might play an important role in the regulation of intracellular pH in vertebrates. In the present study, an NBC cDNA was identified from Pacific white shrimp ( Litopenaeus vannamei ) and designated as Lv-NBC . The full-length Lv-NBC cDNA is 4479 bp in size, containing a 5'-untranslated region (UTR) of 59 bp, a 3′-UTR of 835 bp and an open reading frame (ORF) of 3585 bp that encodes a protein of 1194 amino acids with a deduced molecular weight of 134.34 kDa. The Lv-NBC protein contains two functional domains (Band_3_cyto and HCO3_cotransp) and twelve transmembrane (TM) domains. Expression of the Lv-NBC mRNA was ubiquitously detected in all selected tissues, with the highest level in the gill. By in situ hybridization (ISH) with Digoxigenin-labeled probe, the Lv-NBC positive cells were shown mainly located in the secondary gill filaments. After low or high pH challenge, the transcript levels of Lv-NBC in the gill were found to be up-regulated. After knockdown of the Lv-NBC level by siRNA, the mortality of shrimp significantly increased under pH stress. Our study, as a whole, may provide evidences for the role of NBC in shrimp responding to pH stress, and give a new insight of the acid/base homeostasis mechanism in crustaceans. Highlights: The sodium bicarbonate cotransporter (NBC) cDNA was first isolated from L. vannamei. Lv-NBC mRNA is ubiquitously expressed in all tissues with the highest level in gill. The gill Lv-NBC mRNA was up-regulated after low or high pH challenge. Silencing of Lv-NBC may increase the mortality of shrimp under pH stress.